2014
DOI: 10.1002/cplu.201402090
|View full text |Cite
|
Sign up to set email alerts
|

Direct Oxidative Amidation between N,N‐dimethylanilines and Anhydrides Using Metal‐Organic Framework [Cu2(EDB)2(BPY)] as an Efficient Heterogeneous Catalyst

Abstract: A crystalline porous metal‐organic framework [Cu2(EDB)2(BPY)] was synthesized and used as a heterogeneous catalyst for the direct oxidative amidation between N,N‐dimethylanilines and anhydrides to form tertiary amides as the principal products. The [Cu2(EDB)2(BPY)] exhibited similar activity as compared to that of [Cu2(BDC)2(BPY)], [Cu2(BDC)2(DABCO)], MOF‐143, and other common homogeneous salt catalysts. The optimal reaction conditions employed were [Cu2(EDB)2(BPY)] (10 % mol), TBHP (2 equiv), pyridine (1 equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
(122 reference statements)
0
5
1
Order By: Relevance
“…Thus, the reaction of 1 a and 2 a under the optimized conditions was not affected by the presence of TEMPO, giving 3 aa with the same rate and yield as in the absence of this additive (Scheme 2). It is worthy of note, that this experimental evidence is in contrast with the results by Phan and co-workers, [8] as they reported that no further reaction progress was detected for the same transformation catalyzed by the Cu-MOF [Cu 2 (EDB) 2 (BPY)], after addition of TEMPO.…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…Thus, the reaction of 1 a and 2 a under the optimized conditions was not affected by the presence of TEMPO, giving 3 aa with the same rate and yield as in the absence of this additive (Scheme 2). It is worthy of note, that this experimental evidence is in contrast with the results by Phan and co-workers, [8] as they reported that no further reaction progress was detected for the same transformation catalyzed by the Cu-MOF [Cu 2 (EDB) 2 (BPY)], after addition of TEMPO.…”
Section: Resultscontrasting
confidence: 99%
“…In order to get some information about the plausible mechanistic pathway, and based on previous reports by other authors, [6,8] we next studied the effect of the addition of TEMPO to the reaction mixture as a radical scavenger. Thus, the reaction of 1 a and 2 a under the optimized conditions was not affected by the presence of TEMPO, giving 3 aa with the same rate and yield as in the absence of this additive (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations